Control of conformation in α-helix mimicking aromatic oligoamide foldamers through interactions between adjacent side-chains. Issue 15 (2nd April 2019) - Arrata, Irene; Grison, Claire M.; Coubrough, Heather M.; Prabhakaran, Panchami; Little, Marc A.; Tomlinson, Darren C.; Webb, Michael E.; Wilson, Andrew J.
Abstract : Hydrogen-bonding interactions are used to bias the conformation of an aromatic oligoamide foldamer in favour of an α-helix mimicking syn conformer. Abstract : The design, synthesis and structural characterization of non-natural oligomers that adopt well-defined conformations, so called foldamers, is a key objective in developing biomimetic 3D functional architectures. For the aromatic oligoamide foldamer family, use of interactions between side-chains to control conformation is underexplored. The current manuscript addresses this objective through the design, synthesis and conformational analyses of model dimers derived from 3- O -alkylated para -aminobenzoic acid monomers. The O -alkyl groups on these foldamers are capable of adopting syn - or anti -conformers through rotation around the Ar–CO/NH axes. In the syn -conformation this allows the foldamer to act as a topographical mimic of the α-helix whereby the O -alkyl groups mimic the spatial orientation of the i and i + 4 side-chains from the α-helix. Using molecular modelling and 2D NMR analyses, this work illustrates that covalent links and hydrogen-bonding interactions between side-chains can bias the conformation in favour of the α-helix mimicking syn -conformer, offering insight that may be more widely applied to control secondary structure in foldamers.